Kilovolt GaN MOSHEMT on silicon substrate with breakdown electric field close to the theoretical limit - Ming Tao; Wang, Maojun; Wen, C.P.; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Cheng, Kai; Shen, Bo (2017 29th International Symposium on Power Semiconductor Devices and ICs (ISPSD). Proceedings, 2017)
This work reports a kilovolt and low current collapse normally-off GaN MOSHEMT on silicon substrate. The device with a drift length of 3 mum features a threshold voltage of 1.7 V and an output current of 430 mA/mm at 8 V gate bias. The off-state breakdown voltage (BV) is as high as 1021 V (800 V) defined at a drain leakage criterion of 10 muA/mm with floating (grounded) substrate. The corresponding breakdown electric field is 3.4 MV/cm and the Baliga's figure-of-merit (BFOM) is 1.6 GW/cm2. A small degradation of the dynamic on-resistance (Ron, d) about 30% is observed with a short pulse width of 500 ns and a quiescent drain bias of 60 V. The record value is supposed to benefit from the intrinsic step-graded field plate, high quality LPCVD Si3N4 passivation and material optimization of 4.5 mum thick epitaxial layer.